Preconditions for successful guideline implementation: perceptions of oncology nurses - Yagasaki Kaori; Komatsu Hiroko (BMC, 2011)
Abstract Background Although evidence-based guidelines are important for improving the quality of patient care, implementation in practice is below expectations. With the recent focus on team care, guidelines are intended to promote the integration of care across multiple disciplines. We conducted an exploratory study to understand oncology nurses' perceptions of guideline implementation and to learn their views on how their experiences affected the implementation. Methods A qualitative study was used with focus group interviews. We collected data from 11 nurses with more than 5 years of oncology nursing experience in Japan. The data were analyzed using grounded theory. Results Results of the analysis identified "preconditions for successful guideline implementation" as a core category. There were 4 categories (goal congruence, equal partnership, professional self-development and user-friendliness) and 11 subcategories related to organizational, multidisciplinary, individual, and guideline levels. Conclusions Although the guidelines were viewed as important, they were not fully implemented in practice. There are preconditions at the organizational, multidisciplinary, individual, and guideline levels that must be met if an organization is to successfully implement the guideline in clinical settings. Prioritizing strategies by focusing on these preconditions will help to facilitate successful guideline implementation.